2017
DOI: 10.1007/s00726-017-2393-6
|View full text |Cite
|
Sign up to set email alerts
|

Amino acids intake and physical fitness among adolescents

Abstract: The aim was to investigate whether there was an association between amino acid (AA) intake and physical fitness and if so, to assess whether this association was independent of carbohydrates intake. European adolescents (n = 1481, 12.5–17.5 years) were measured. Intake was assessed via two non-consecutive 24-h dietary recalls. Lower and upper limbs muscular fitness was assessed by standing long jump and handgrip strength tests, respectively. Cardiorespiratory fitness was assessed by the 20-m shuttle run test. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 41 publications
2
13
0
1
Order By: Relevance
“…In this study, no relationship was found between dietary intake, physical activity score and hand grip strength among female adolescents. This result is similar to that reported in a study on adolescents in Europe,15 which showed that proline (amino acids) is positively correlated with lower limb muscular strength but that, when carbohydrate intake is controlled for, this relationship disappears 15. On the other hand, a study conducted among Kenya adolescents found that female adolescents have greater muscle strength than their male counterparts and suggested that this was because the females undertake more household chores such as transferring water from deep wells and preparing meals, and thus have greater access to food than the males 54.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, no relationship was found between dietary intake, physical activity score and hand grip strength among female adolescents. This result is similar to that reported in a study on adolescents in Europe,15 which showed that proline (amino acids) is positively correlated with lower limb muscular strength but that, when carbohydrate intake is controlled for, this relationship disappears 15. On the other hand, a study conducted among Kenya adolescents found that female adolescents have greater muscle strength than their male counterparts and suggested that this was because the females undertake more household chores such as transferring water from deep wells and preparing meals, and thus have greater access to food than the males 54.…”
Section: Discussionsupporting
confidence: 93%
“…We cannot exclude the influence of fasting condition at the time of blood sampling in the amino acid plasma levels, given the fact that some of the amino acids are taken by diet, and that previous evidence demonstrated positive associations between food consumptions and altered profile of amino acids 5 , 71 . In addition, we do not have data concerning the physical activity of the participants, which can also impact the amino acids profile 72 , 73 similar to information about metabolic diseases as dyslipidemia and diabetes mellitus. Third, our patients were not drug-naïve and were heterogeneous regarding the type and duration of pharmacological treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This study provides the first Malaysian population estimates of HGS, a marker of overall muscle strength, dietary intakes and physical activity, and it tracked the changes of these variables over time in the same individuals from early adolescence (13 years) to middle (15 years) and late adolescence (17 years). Often, these cohort studies were analysed as cross-sectional looking either at a single nutrient (15) , on dietary pattern (16) , or adherence to Mediterranean diet only (14) . Furthermore, the longitudinal design of this study has allowed the researcher to investigate the longitudinal relationship between the key variables of interest.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…cross-sectionally. Some dietary studies have shown beneficial effects of the Mediterranean diet (14) , while others have shown no effects of single nutrient (15) or food groups (16) on muscle strength. While a population-based cohort study had concluded lower physical activity is associated with lower hand grip strength (HGS) for both sexes (17) .…”
mentioning
confidence: 99%